Priesthood and temple in John's apocalypse: constructing the sanctuary - Tse, Timothy B. (Library of New Testament studies, 2025)
"Timothey B. Tse argues that, while John uses language drawn from the Hebrew Bible's descriptions of YHWH's dwelling place, scholarship has overlooked the importance of his spatial transformation of that language. Tse thus uses theories relating to Relevance, Resistance Theory, Critical Space Theory, and Conceptual Metaphor, to demonstrate that a significant part of John's apocalyptic strategy of resistance is to re-present his vision to his audience spatially, so that they can experience a divinely ordained alternative to the world in which they live. Tse first demonstrates John's attempts to relegate his audience's experience of space to his revelation: John's description of the visionary world creates the metaphors 'the earth is a Sanctuary' and 'the Saints are its priests.' Tse argues that, under this view, life on earth must be evaluated according to the concerns of the Sanctuary, which by definition requires the removal of everything impure, and the Saints (namely all Christians in both the historic and visionary worlds) must take priestly responsibility for the earth. John therefore portrays the Saints joining in the removal of all impurity upon the earth by fighting, as priests, in God and the Lamb's war against Satan, Babylon, and all her impurities. Tse concludes that, overall, John means to realign the church's experience of space, so that they understand themselves as priests of the Sanctuary, and to live according to that reality. " --